Trade-Growth Nexus in Landlocked Developing Countries: A Quantile Regression Framework - Paudel, Ramesh Chandra (Economic Journal of Nepal, 2019)
This paper investigates the trade growth nexus in landlocked developing countries. Landlockedness imposes exogenous costs to a country making import more expensive and exports uncompetitive. Despite this fact, landlocked countries also are in the process to be integrated with world but in slow pace. Initial income is one of the major determinants of economic growth in these countries whether they are poor or rich now, however, negative impact of Landlockedness seems more severe in economic growth of poor countries. Trade has a positive role in landlocked countries too to trade than the poor countries. Neighbour countries’ economic growth has level increases, it shifts towards industrialisation so that capital formation is more important compared to labour force until the economy converges to the developed economy.